IMPACTS OF DEFORESTATION ON ANIMAL AND PLANT BIODIVERSITY IN TROPICAL ECOSYSTEMS - Austríaco-Teixeira, Phelipe; Rossato, Domenika Rubert; Correa, Renara Fabiane Ribeiro; Albuquerque, Álisson Rangel (Editora Impacto Científico, 2025)
Biodiversity conservation in tropical ecosystems constitutes a fundamental challenge of contemporary times, especially given the accelerated expansion of deforestation caused by anthropogenic activities. This study analyzes the impacts of deforestation on animal and plant biodiversity in tropical ecosystems, investigating mechanisms through which vegetation cover loss affects species diversity and ecological processes. The research is justified by the need to systematize knowledge about the consequences of habitat fragmentation for tropical fauna and flora conservation, providing support for environmental public policies. The general objective consists of analyzing the main impacts of deforestation on tropical biodiversity. Methodologically, a qualitative exploratory approach is adopted through systematic literature review in international scientific databases, with thematic content analysis of 54 selected articles. Results show that habitat fragmentation compromises population viability of species, reduces genetic variability, and alters fundamental ecological processes such as nutrient cycling and pollination. It is concluded that integrated conservation strategies, including protected areas, agroforestry systems, and ecological restoration, prove essential to mitigate deforestation effects, although the effectiveness of these strategies depends on political commitment, substantial investments, and engagement of local communities. DOI: https://doi.org/10.56238/edimpacto2025.088-001